Pencegahan Korupsi Dana Desa (Studi Pada Kantor Desa Sekarwangi Kecamatan Cibadak Kabupaten Sukabumi Jawa Barat) - Vera Rimbawani Sushanty; Gatot Efrianto; Rachmat Pramukty; Arfian Arfian; Heru Irianto; Bambang Rudiansyah (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
This research aims to determine efforts to prevent corruption in village funds in Sekarwangi Village, Cibadak District, Sukabumi Regency, West Java. This research uses a descriptive method with a qualitative approach. Data collection through interviews with Village Heads and Financial Planning Staff. This research states the modus operandi for misappropriating village funds, the village head's efforts to minimize opportunities for misappropriation or corruption of village funds. The modus operandi includes the preparation of the RAB which is not in accordance with the agreement at the village meeting, the accountability of the village head which is not in accordance with the funds used, the village head who borrows village funds for reasons but is not returned, official trips which are never carried out, inflated incentives for equipment. villages and others. The village head's efforts to minimize opportunities for misappropriation or corruption of village funds include when compiling and allocating village funds through deliberation, payments for development purposes through transfers, there must be inscriptions or banners containing information about a project being built, the village head and village officials must be firm, work on development projects is carried out by the community, the community carries out supervision through PTPKD, increases the capacity building of village officials, training for village heads and their staff, strengthening the capacity of village assistants, reducing regional government interference and optimizing the role of existing organizations in the village.